Unravelling the genesis and depositional setting of Neoproterozoic banded iron formation from central Eastern Desert, Egypt - Sami, Mabrouk; Faisal, Mohamed; Leybourne, Matthew; Sanislav, Ioan V.; Ahmed, Mohamed S.; Lasheen, El Saeed R. (Frontiers in Earth Science, 2024)
The Neoproterozoic banded iron formations (BIFs) are widely occurred in the Egyptian Eastern Desert. This study integrates field observations, petrographic studies, geochemical data, and lead isotopes to construct the genesis and depositional environment of Wadi El-Mishama BIF deposits. The iron layers, primarily of oxide facies within a volcano-sedimentary sequence, comprise magnetite-rich beds alternating with jaspilite or silicate laminae. The studied BIFs exhibit a dominant composition of SiO2 and Fe2O3 t with relatively low contents of TiO2 and Al2O3. The positive correlation of REEs (La, Sm, Yb) with Zr and low concentrations of HFSEs (Ta, Nb, Th, Hf) indicate a primary formation mechanism of chemical precipitation, maintaining original geochemical signatures. Geochemical patterns show depletion in LREEs, enrichment in HREEs (La/YbPAAS = 0.08-0.12), and positive La anomalies (La/LaPAAS = 1.15-8.57), consistent with seawater influence. Additionally, various geochemical discrimination diagrams supported by elevated super-chondritic Y/Ho values (29.6-38.7), weak positive Eu anomalies, and low contents of transition metals (Cu and Zn), point to the interaction of low-temperature (<200 °C) hydrothermal fluids (bearing Fe and Si) with seawater during the deposition of the BIFs. The lack of significant negative Ce anomalies along with low Ni/Co, U/Th, and Cu/Zn ratios, imply that the iron mineralization was precipitated from dysoxic to oxic conditions. The geochemical and Pb isotopic data suggest that the iron deposits formed in an extensional geodynamic setting (intra-oceanic arc basin environment) due to the subduction of the Mozambique Plate, with signatures closely matching other Precambrian Algoma-type BIFs.